PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KECENDERUNGAN PERILAKU AGRESIF PESERTA DIDIK DI MA - Fitri Hayati (UNIVERSITAS BENGKULU, 2016)
This research method a qualitative descriptive research. Subject and object in this research is the principal, headmaster ,teacher guidance and counseling and student. Insrumen usedin this study were interviews, observation and documentation. The results showed that (1) the cause learners to behave aggressive is largely because the character of the students were loud and tend to assumes that the behavior they are doing is a fairness and because the lack of supervision, attention and affection from parents so that children tend to feel able to do any desired and (2) the role of the teacher guidance and counseling in reducing aggressive behavior students is good enough to provide individual counseling.Keyword: teacher, guidance and counseling, aggresive